Description and Nomenclature of Neisseria meningitidis Capsule Locus - Odile B. Harrison; Heike Claus; Ying Jiang; Julia S. Bennett; Holly B. Bratcher; Keith A. Jolley; Craig Corton; Rory Care; Jan T. Poolman; Wendell D. Zollinger; Carl E. Frasch; David S. Stephens; et al. (Emerging Infectious Diseases, 2013)
Pathogenic Neisseria meningitidis isolates contain a polysaccharide capsule that is the main virulence determinant for this bacterium. Thirteen capsular polysaccharides have been described, and nuclear magnetic resonance spectroscopy has enabled determination of the structure of capsular polysaccharides responsible for serogroup specificity. Molecular mechanisms involved in N. meningitidis capsule biosynthesis have also been identified, and genes involved in this process and in cell surface translocation are clustered at a single chromosomal locus termed cps. The use of multiple names for some of the genes involved in capsule synthesis, combined with the need for rapid diagnosis of serogroups commonly associated with invasive meningococcal disease, prompted a requirement for a consistent approach to the nomenclature of capsule genes. In this report, a comprehensive description of all N. meningitidis serogroups is provided, along with a proposed nomenclature, which was presented at the 2012 XVIIIth International Pathogenic Neisseria Conference.